2006
DOI: 10.1002/jor.20220
|View full text |Cite
|
Sign up to set email alerts
|

Retraining cervical joint position sense: The effect of two exercise regimes

Abstract: This study compared the effects of conventional proprioceptive training and craniocervical flexion (C-CF) training on cervical joint position error (JPE) in people with persistent neck pain. The aim was to evaluate whether proprioceptive training was superior in improving proprioceptive acuity compared to another form of exercise, which has been shown to be effective in reducing neck pain. This may help to differentiate the mechanisms of effect of such interventions. Sixty-four female subjects with persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
186
1
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(217 citation statements)
references
References 38 publications
14
186
1
16
Order By: Relevance
“…The advantages to the groups who performed the specific neck exercises and especially those that included a behavioural approach is likely due to the intervention addressing some of the possible causes of altered cervical afferent input, such as neck pain, muscle fatigue, altered neuromotor control and improvement of psychological distress and kinesiophobia that may have led to the symptom of dizziness and changes in sensorimotor control. Previous research has suggested that improving neck muscle endurance improves postural stability in those with WAD (Stapley et al , 2006) and that exercises to address neuromotor control of the deep neck flexor (DNF) musculature improves HRA and/or dizziness in those with neck pain (Jull et al , 2007) ( Thoomes-de Graaf and Schmitt, 2012). Similarly reduction in pain can influence balance measures (Dehner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages to the groups who performed the specific neck exercises and especially those that included a behavioural approach is likely due to the intervention addressing some of the possible causes of altered cervical afferent input, such as neck pain, muscle fatigue, altered neuromotor control and improvement of psychological distress and kinesiophobia that may have led to the symptom of dizziness and changes in sensorimotor control. Previous research has suggested that improving neck muscle endurance improves postural stability in those with WAD (Stapley et al , 2006) and that exercises to address neuromotor control of the deep neck flexor (DNF) musculature improves HRA and/or dizziness in those with neck pain (Jull et al , 2007) ( Thoomes-de Graaf and Schmitt, 2012). Similarly reduction in pain can influence balance measures (Dehner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that programs that emphasize gaze stability, eye head co-ordination and cervical position sense and balance tasks without local cervical spine treatment have resulted in either decreased medication intake, improved neck pain and disability, HRA and or balance in those with neck pain (Revel et al , 1994, Fitz-Ritson, 1995, Humphreys and Irgens, 2002, Jull et al, 2007, Treleaven, 2010. Improvements in balance and symptoms of dizziness have also been observed following a vestibular or oculomotor rehabilitation program or tailored sensorimotor program in patients with persistent WAD (Hansson et al , 2006, Storaci et al , 2006, Treleaven, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings reveal for the first time a positive effect of neck muscle vibration on impaired joint position sense acuity in patients with neck pain. For patients, different long-term treatments have previously been shown to improve repositioning accuracy: conscious head relocation tasks [26], chiropractic care [27], and balance training [28]. All these interventions took place over a period of several weeks.…”
Section: Joint Position Sensementioning
confidence: 99%
“…As the body's center for controlling balance is located within the inner ear, neck position sense is vital in the control and maintenance of balance [23].…”
Section: Discussionmentioning
confidence: 99%